Idiopathic inflammatory myopathies: a review. Issue 6 (21st June 2021) - Ashton, Catherine; Paramalingam, Shereen; Stevenson, Brittany; Brusch, Anna; Needham, Merrilee
Abstract: Idiopathic inflammatory myopathy (IIM) is the umbrella term including dermatomyositis (DM), polymyositis (PM), overlap myositis (OM), sporadic inclusion body myositis (IBM) and necrotising autoimmune myopathy (NAM), also known as immune‐mediated necrotising myopathy. There is some debate as to whether PM exists as a discrete entity, or perhaps is an overly generalising term encompassing connective tissue disease associated myositis, or OM, and the previously poorly recognised NAM. As such, PM will not be covered in detail in this review. DM, OM and NAM all present similarly, with proximal weakness and elevated creatine kinase (CK) level. By contrast, IBM preferentially involves the long finger flexors and quadriceps, and presents with a normal or only mildly elevated CK. Developments in serological testing and imaging are shifting the diagnostic paradigm away from a reliance on histopathology. The therapeutic armamentarium for IIM continues to evolve, with intravenous immunoglobulin and rituximab proving to be successful for refractory disease. This review will provide a diagnostic algorithm for the clinician to help distinguish between IIM subtypes – with emphasis on clinical assessment, serology and imaging, as well as discussion of therapeutic options and escalation of immunotherapy.